2020
DOI: 10.1063/5.0021338
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic investigation of moisture-induced degradation of methylammonium lead iodide

Abstract: We performed in situ x-ray diffraction (XRD) experiments on an inorganic-organic hybrid perovskite, CH 3 NH 3 PbI 3 (MAPbI 3 ), during its interaction with moisture to understand the degradation mechanism. Although the degradation of inorganic-organic hybrid perovskite is an important factor hampering their development as solar cell materials, understanding of the degradation process is currently limited. The moisture-induced degradation mechanism was revealed by the temperature dependence of the in situ XRD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…[ 45 ] In addition to the (CH 3 NH 3 ) 4 PbI 6 .2H 2 O hydrate, another degradation product of monohydrate MAPbI 3 · H 2 O (Equation (1)) was found under high humidity environment (80% RH), along with the additional grain boundaries. [ 46,47 ] Likewise, our previous work also revealed that moisture induced the formation of metastable hydrate phases along with the domain swelling ( Figure 3 a), thus giving rise to the round and pebble‐like crystals (Figure 3b). [ 42 ] The moisture‐induced hydration process is always accompanied by the structure change from 3D crystals to 1D structure and 0 D framework.…”
Section: Moisture Effects On Perovskitesmentioning
confidence: 61%
“…[ 45 ] In addition to the (CH 3 NH 3 ) 4 PbI 6 .2H 2 O hydrate, another degradation product of monohydrate MAPbI 3 · H 2 O (Equation (1)) was found under high humidity environment (80% RH), along with the additional grain boundaries. [ 46,47 ] Likewise, our previous work also revealed that moisture induced the formation of metastable hydrate phases along with the domain swelling ( Figure 3 a), thus giving rise to the round and pebble‐like crystals (Figure 3b). [ 42 ] The moisture‐induced hydration process is always accompanied by the structure change from 3D crystals to 1D structure and 0 D framework.…”
Section: Moisture Effects On Perovskitesmentioning
confidence: 61%
“…[20] According to this, it has been shown that HP materials degrade along these sites when both moisture and trapped charges exist simultaneously. [20] Particularly, the presence of water molecules which are known to form hydrates [21,22] allowing charges trapped at the defect site to easily deteriorate the HPs structure. In addition, the aforementioned sites are considered as one of the main reasons for the appearance of hysteresis as defects could provide a favorable pathway for ion migration due to reduced steric hindrance.…”
mentioning
confidence: 99%